Transformation of LEGO Models. Issue 6 (2nd November 2018) - Pan, Wei; Chen, Lujie
ABSTRACT: Container stacking is a common activity in various industries. At a large scale, the shipping industry stacks cargo containers, while at a smaller scale the home and office storage providers stack paper or plastic boxes. An interesting question behind container stacking is how to efficiently move containers from one stack to another. In this paper, we investigate a remotely related question: shape transformation between LEGO models. While many computational algorithms have been developed to construct LEGO models, the problem of constructing a LEGO model using bricks from an existing model has not been explored in open literature. We propose two objectives to optimize the transformation: the movement cost and the reuse rate of LEGO bricks. Two basic approaches coupled with three strategies are implemented to achieve shape transformation. Experiments and analysis reveal the efficiency of diﬀerent algorithms under several metrics of evaluation. GRAPHICAL ABSTRACT: